Australian postwar immigration - COCHRANE, D. (PSL Quarterly Review, 2014)
Large scale migration has been an important economic and social phenomenon in the post-war world, and Australia’s role in this regard has been a very prominent one. With regard to population, Australia has absorbed a higher percentage of migrants than any other country during the period 1945 to 1954. The present article provides an in-depth analysis of such post-war immigration. The author first breaks down the nationality of immigrants, their method of arrival, their age and sex, and their occupations. The reasons behind Australia’s immigration policy and the economic effects and implications of immigration in Australia are then considered. JEL: J15, J61, K37